HUBUNGAN BERAT BADAN BAYI BARU LAHIR DENGAN KEJADIAN RUPTUR PERINEUM PADA PERSALINAN NORMAL DI RSI IBNU SINA BUKITTINGGI TAHUN 2014 - Media Fitri, Media Fitri; Tuti Oktriani, Tuti Oktriani (Jurnal Kesehatan - STIKes Prima Nusantara, 2015)
The main cause of postpartum is hemorrhage 40% of maternal mortality include haemorrhage caused by a ruptured perineum. Rupture of the perineum is torn birth canal accidentally due to incorrect position of labor and the weight of the baby is too big. The purpose of this research is to reduce the maternal mortality rate by 2014. The research method is analytical survey with cross sectional design. The population in this study are all normal birth mothers for 33 people. The sampling method used is accidental sampling technique univariate analysis to describe the characteristics of respondents, bivariate analysis to determine the relationship of weight newborns with perineal rupture in normal delivery using a statistical test Chi square. Most respondents weight babies with normal birth weights (2500-4000 grams) of 27 (81.8%) and in getting the majority of mothers who suffered 2nd degree perineal rupture is a tear with extension into the vaginal mucosa, posterior commissure, the skin of the perineum and perineal muscles for 20 (60.6%) normal birth mothers. The result showed a significant value of p = 0,00 of the known value of p